Performance Comparison Grounding System using Aluminium and Copper - Nik Hassan, Nik Hamizan Hakim; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2025)
This study presents a comparative analysis of aluminum and copper as grounding materials by evaluating their effectiveness through soil resistance measurements. Prototype grounding systems—including single rod, triple parallel rods, and grid configurations—were installed at a depth of 1.5 meters at an open field site at Universiti Tun Hussein Onn Malaysia (UTHM). Resistance values were recorded daily over 30 days using the Fall-of-Potential method. The results indicate that for the single rod configuration, copper exhibited a slightly lower average resistance (4.50 Ω) compared to aluminum (4.95 Ω). In the triple parallel rod setup, aluminum outperformed copper with an average resistance of 1.17 Ω versus 1.41 Ω. For the grid configuration, aluminum again demonstrated superior performance with an average resistance of 2.52 Ω, while copper recorded 3.51 Ω. These findings suggest that aluminum is a viable and often more effective alternative to copper in certain grounding system configurations, particularly in grid installations.